The Role of Librarians as Digital Curators in the Digital Information Era in the Muhammadiyah University of North Sumatra Library - Nursalimah, Annisa; Ali, M. Nasihudin (Journal La Edusci, 2024)
This research aims to analyze the role of librarians as digital curators in the digital information era at the Muhammadiyah University of North Sumatra Library. In this research the author used a qualitative research method with a case study approach. The case study used aims to provide readers with an understanding of the role of librarians as digital curators in the digital information era. In the era of globalization, libraries must adapt to information technology to provide fast and accurate information. Librarians as digital curators play an important role in collecting, managing and maintaining relevant digital collections. Digital libraries allow access to information without physical boundaries. At the Muhammadiyah University of North Sumatra (UMSU) Library, librarians help users access digital information and provide training in using digital resources. This research analyzes the role of librarians as digital curators, their impact in managing collections and information services, as well as the challenges faced in the digital information era.